2018
DOI: 10.5812/archcid.55099
|View full text |Cite
|
Sign up to set email alerts
|

Colistin-Resistant Klebsiella pneumoniae: Prevalence of Integrons and Synergistic Out Turn for Colistin-Meropenem

Abstract: Background: Klebsiella pneumoniae has the potential to disseminate at speed among the hospital environment, hence included as a major nosocomial pathogen causes of severe infections. This work mainly focused on finding out the prevalence of different classed of integrons in colistin-resistant Klebsiellapneumoniae and to analyze the efficacy of colistin-meropenem in combination. Methods: For this cross-sectional study, random non-biased sampling technique was followed and non-repetitive, Kleb-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…It would be highly dangerous as it might be challenging to curb the spread if not taken properly measures and impede antibiotic therapy. 28 Also, it agrees with another report, which showed that the availability of class 1 integron in the MDR strains could have an impact on the dispersal of clustered resistance genes. 35 The detection of hypermucoviscous (HMV) phenotype is feasible and can be easily performed in any microbiology laboratory.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…It would be highly dangerous as it might be challenging to curb the spread if not taken properly measures and impede antibiotic therapy. 28 Also, it agrees with another report, which showed that the availability of class 1 integron in the MDR strains could have an impact on the dispersal of clustered resistance genes. 35 The detection of hypermucoviscous (HMV) phenotype is feasible and can be easily performed in any microbiology laboratory.…”
Section: Discussionsupporting
confidence: 90%
“…But mcr (1-5) genes were not detected, which shows a lack of plasmid-mediated resistance, which is similar to our previous report. 28 The colistin resistance could be due to chromosomal-mediated such as alteration in the LPS target, high mucous production, or biofilm formation. 29 Through genome sequencing, no unique alternations were identified in colistin-resistant isolates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the combination of two last-resort antibiotics, colistin and meropenem, showed a synergistic effect against four MDR K. pneumoniae. Although earlier studies showed synergy of the colistin-meropenem combination [28], this is one of the first against the clinical isolates collected from Mizoram. These results again support the combinational activity of two antibiotics against resistant bacterial pathogens.…”
Section: Discussionmentioning
confidence: 84%
“…Interestingly, there have been other reports showing colistin-resistant isolates not harbouring mcr genes. In the study by Manohar et al, 24 colistin-resistant Klebsiella pneumoniae isolates were investigated and none of them carried mcr-1 or mcr-2 [37]. Potentially, this could be due to the loss of LPS as recently shown by mutations in lipid A biosynthesis genes in E. coli [38].…”
Section: Plos Onementioning
confidence: 99%